2004
DOI: 10.1097/00006454-200404000-00009
|View full text |Cite
|
Sign up to set email alerts
|

Postnatally acquired cytomegalovirus infection via breast milk: effects on hearing and development in preterm infants

Abstract: The results of this study suggest that early postnatally acquired CMV infection via CMV-positive breast milk does not have a negative effect on neurodevelopment and hearing in this group of patients. Because we studied a small number of infants, further follow-up studies are warranted in preterm infants with early postnatally acquired CMV infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
112
0
9

Year Published

2004
2004
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 138 publications
(122 citation statements)
references
References 14 publications
1
112
0
9
Order By: Relevance
“…18,42 These benefits appear to outweigh the risks of severe disease from breast milk-acquired CMV infection in the neonatal period, which has not been definitively associated with the delayed development or sensorineural hearing loss seen with congenital CMV infection. 2,11,13,26,[43][44][45] However, long-term follow-up data on the effects of postnatal CMV infection are limited, with only a small number of infants studied into childhood. One recent study found that the cognitive and motor function scores of VLBW infants with breast milk-acquired CMV infection were within normal ranges when examined at school age but not as high as those of the controls (VLBW infants without CMV infection).…”
Section: Figurementioning
confidence: 99%
“…18,42 These benefits appear to outweigh the risks of severe disease from breast milk-acquired CMV infection in the neonatal period, which has not been definitively associated with the delayed development or sensorineural hearing loss seen with congenital CMV infection. 2,11,13,26,[43][44][45] However, long-term follow-up data on the effects of postnatal CMV infection are limited, with only a small number of infants studied into childhood. One recent study found that the cognitive and motor function scores of VLBW infants with breast milk-acquired CMV infection were within normal ranges when examined at school age but not as high as those of the controls (VLBW infants without CMV infection).…”
Section: Figurementioning
confidence: 99%
“…A recent study suggested less favorable cognitive and motor function outcomes in preterm infants with postnatally acquired CMV infection, as compared with those without CMV infection, 47 but other studies have not demonstrated an increased risk. 48 Future clinical studies are needed to determine whether the appearance of DNAemia in asymptomatic preterm infants is predictive of the development of end-organ disease, and to assess whether there are any short-or long-term benefits to be realized from the use of preemptive antiviral interventions, such as GCV and/or CMV immune globulin, in the absence of clinical evidence of CMV disease.…”
Section: Figurementioning
confidence: 99%
“…Entretanto, visto o pequeno número de crianças avaliadas, estudos de acompanhamento em prematuros com infecções adquiridas no perí-odo pós-natal são necessários 34 .…”
Section: Citomegaliaunclassified